Schistosomiasis in a Scottish school group after freshwater swimming in Uganda: the need to raise awareness. (25th September 2018) - Currie, Sandra L.; Denvir, Lucy; Mooka, Busi; Perrow, Kali; Alexander, Claire L.
Abstract : Introduction. Schistosomiasis, a travel-related trematode infection, can cause a range of symptoms with potentially life-threatening complications. In this report, we describe an outbreak of schistosomiasis in a Scottish school group that had travelled to Uganda. We discuss the requirement for robust and accurate pre-travel advice, and the importance of raising awareness in travellers, particularly due to the asymptomatic nature of the disease. In addition, we highlight the need to submit a serum sample for laboratory testing on return from endemic regions where freshwater exposure has occurred. Case presentation. A Scottish school group consisting of 19 individuals visited Uganda during July 2016 with one positive symptomatic case identified on return to the UK. As three of the individuals were not Scottish residents, their data were excluded from this report. Freshwater exposure was noted from taking part in activities which included swimming in the Nile. The Scottish Parasite Diagnostic and Reference Laboratory performed serology testing using sera from 16 Scottish residents to detect IgG towards Schistosoma egg antigens. Thirteen were positive despite only one case being symptomatic. Conclusion. The high positivity rate raised several issues. These included the lack of a robust risk assessment by the travel company organizing the trip, the lack of awareness of schistosomiasis by some individuals, the lack of appropriate and accurate pre-travel advice, and the asymptomatic nature of the infection. This report provides supportive evidence to strengthen the need for improvements to prevent largely asymptomatic cases being missed in future.